Moral injury experienced by emerging adults with child welfare histories in developmental and sociocultural contexts: "I knew the system was broken.". (August 2022) - Haight, Wendy; Cho, Minhae; Soffer-Elnekave, Ruth; Nashandi, Ndilimeke J.C.; Suleiman, Johara
Highlights: Emerging adults described experiences of moral injury as children and youth in the child welfare system. Child maltreatment, failure to protect, and injury of identity were morally injurious. Types and meanings of morally injurious events varied with development. Moral injury was perpetrated by participants, birth and foster families and child welfare professionals. BIPOC children and youth experienced unique vulnerabilities to moral injury. Abstract: This mixed methods research examines moral injury in childhood and adolescence as described by emerging adults with histories of child welfare involvement. Twenty-eight emerging adults (18–25 years) with foster care histories participated in life story interviews, and assessments of exposure to potentially morally injurious events (Moral Injury Events Scale, MIES; Nash et al., 2013 ). Participants reported on the MIES exposure to potentially morally injurious events during their involvement in the child welfare system as children and adolescents. The most common events described by participants were child maltreatment (82%), adults' failure to protect them (75%), and injury to their identities as individuals worthy of respect, and as members of particular groups (families, ethnic communities) (39%). In addition, most participants reported multiple moral injuries, and moral injuries that were sustained across months or years. Participants' reported responses to these events included: rage, shame, guilt, and feelings of betrayal, vulnerability, confusion and worthlessness. Longer term responses included relationship problems, mental health and substance abuse disorders. Perpetrators of moral injury included parents, substitute caregivers, and child welfare professionals. Events occurred in birth homes, but also in out-of-home placements and social service settings. This study contributes to child welfare by highlighting the voices of young people, and identifying moral as an issue for practice and policy intervention. In so doing, this research also contributes to the literature on moral injury by examining the lived experiences of individuals reporting moral injury, by extending the concept to emerging adults with child welfare histories, and by considering moral injury in developmental and sociocultural contexts.